Understanding the dynamics of English in the linguistic landscapes of Guangzhou / Junhua Peng … [et al.] - Peng, Junhua; Mansor, Nor Shahila; Ang, Lay Hoon; Mohd Kasim, Zalina (Universiti Teknologi MARA, 2021)
Linguistic landscape is a study field covering all linguistic objects in public spaces. It provides an important perspective for investigating the dynamics of social life and language change in given territories. Guangzhou, a significant commercial center in southern China, is renowned for its globalized development. With the growth of globalization, the increasing intrusion of English and the emerging English varieties have occurred in the urban linguistic landscapes of Guangzhou City. Therefore, this descriptive qualitative study collected English usage in the public sphere by taking pictures of private signs in two commercial centers. Monolingual and bilingual public signage displayed in public spaces shows that English has been an important foreign language widely used in Guangzhou's cityscape. Meanwhile, the use of English in Guangzhou is somewhat affected by local languages, a phenomenon called glocalization. The misuse of English, code-mixing between Chinese and English, and emerging English varieties are the product of glocalization. This study can shed light on the present linguistic situation of English in Guangzhou. Additionally, it provides evidence for the development process of glocalized English and translanguaging practice in southern Chinese communities.